Determinação da contaminação fúngica do ar em Creches Públicas do Rio de Janeiro/RJ / Determination of air fungal contamination in public kindergartens in Rio de Janeiro/ RJ - Érica Mendonça Ziehe; Renata Buarque Fernandes; Marta Ribeiro Valle Macedo; Valéria Michielin Vieira; Aurea Maria Lage de Moraes (Fundação Oswaldo Cruz (FIOCRUZ), 2014)
Este artigo apresenta a avaliação quantitativa e qualitativa dos contaminantes ambientais de duas creches no Estado do Rio de Janeiro. Uma das creches funciona em um andar do prédio administrativo de um Hospital Federal e a outra foi instalada em uma edificação mais nova e construída para essa função. Foram escolhidos três pontos de coleta na creche A e quatro pontos na creche B durante as quatro estações do ano - primavera, verão, outono e inverno. Comparamos os ambientes internos e avaliamos a variabilidade dos parâmetros entre as duas creches durante as estações. Os níveis de contaminação eram próximos em ambas as creches. Foi observado que a maioria das áreas internas avaliadas tinha o nível de contaminação igual ou superior à contaminação externa. ------------------------------------------------------------------------------ This note presents measurements of fungal contaminants in two public nursery schools in Rio de Ja-neiro state, Brazil. One of the nursery school operates in an adapted floor in a building that belongs to the administrative sector of a federal hospital; the other is newer and was designed to be a nursery school. Measurements were obtained for airborne fungi, temperature and relative humidity. Each of these measurements was made in three points in nursery school A and four points in school B over four seasons - spring, summer, fall and winter. We compared the indoor environments and examined the variability in measured parameters between and within schools and across seasons. The level of all measured parameters was comparable for the two schools. It was observed that in the majority of the evaluated areas the indoor contamination was close to or superior to the outdoor contamination.